Miscanthus interspecific hybrids exceed the biomass yield and quality of their parents in the saline–alkaline Yellow River delta. (27th November 2021) - Zheng, Cheng; Xiao, Liang; Iqbal, Yasir; Sun, Guorong; Feng, Hui; Liu, Fulai; Duan, Meijuan; Yi, Zili
Abstract: The genus Miscanthus is a promising lignocellulosic feedstock crop for the production of bioenergy. Miscanthus is drawing attention because it can be grown on marginal land and avoid competition with food crops. Therefore, as measures of performance, biomass yield and quality of two parent species ( Miscanthus sinensis and Miscanthus lutarioriparius ) and 15 of their interspecific hybrids were evaluated in a saline–alkaline soil of the Yellow River delta in China. Ethanol and biogas production potentials were also estimated. A field trial with a randomised block design with five replicates of each genotype was conducted in 2014. Biomass yield, plant height, tiller number, stem diameter, and tiller mass of each parent and hybrid were measured at the end of the growing season in 2015, 2016, and 2017. Quality traits, including cellulose, hemicellulose, lignin and ash contents, were measured. There was large genotype variation in biomass yield and in most of the biometric parameters, and cellulose (range: 0.33 to 0.45 g/g), hemicellulose (0.32 to 0.43 g/g), lignin (0.07–0.13 g/g) and ash (0.02–0.06 g/g) contents were significantly different among the hybrids. The ash content of all hybrids was significantly lower than that of M . sinensis . The two‐year (2016 and 2017) average biomass yield of the 15 hybrids ranged from 9.87 to 23.11 t/ha, which was significantly higher than that of either parent ( M . sinensis : 1.20 t/ha; M . lutarioriparius : 3.87 t/ha). Two hybrids, SL8 and SL15, were identified as potential genotypes suitable for the saline–alkaline soils of the Yellow River delta. These results demonstrate that interspecific hybridisation is crucial to improve Miscanthus biomass yield and quality under marginal conditions. Abstract : No miscanthus genotype currently was suitable for growing in saline–alkaline soil. In this study, fifteen interspecific hybrids were developed in the saline–alkaline soil in the Yellow River Delta, and their biomass yield ranged from 9.87 to 23.11 t/ha. Taking biomass yield and quality of hybrids into consideration, two hybrids, SL8 and SL 15, were identified as the potential genotypes suitable for growing in the saline–alkaline Yellow River Delta.